POLITICAL LEGAL FORMATION OF LEGAL REGULATIONS USING THE CARRY-OVER MECHANISM AND ITS RELATIONSHIP TO GENERAL PRINCIPLES OF GOOD GOVERNMENT - Mohammad Raihan; Qurrata Ayuni; David Aprizon Putra (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
Legal politics in the formation of a draft law into law requires a mechanism with a process that is not simple. The process of forming statutory regulations is regulated in Law Number 15 of 2019 concerning the Formation of Legislative Regulations. The planning and preparation stage begins with the National Legislation Program (Prolegnas). In the Prolegnas, it is planned and prepared an agenda for any bills which will be the task of the House of Representatives to be discussed for the next 1 (one) to 5 (five) years and are only valid during the term of office of the DPR in that period. Therefore, a mechanism for "inheriting" the bill from the previous period to the next period is needed to ensure the continuity of the bill discussion process or it can be called a " carry-over " mechanism which basically has the main objective of continuing the discussion of the bill so that it reaches the enactment stage. raised in this paper is "What is the process of forming legislation with a carry-over mechanism and its relationship to the general principles of good governance?" The research method used in this journal is normative legal research method, which refers to legal norms contained in laws and court decisions, as well as legal norms prevailing in society. The results of this research show that Prolegnas, as the first step in determining what bills can be drafted using the carry over concept , is a form of legal politics in the formation of laws. It is hoped that the formation of laws through the carry-over concept can perfect the process of forming laws and regulations that pay attention to the effectiveness and sustainability of development planning and are in accordance with the formation of good laws and regulations. Keywords: Legal Politics, Draft Law, Carry-Over.